2016
DOI: 10.4315/0362-028x.jfp-15-485
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Some Human Enteroparasites in Commonly Consumed Raw Vegetables in Tabuk, Saudi Arabia

Abstract: The problem of parasitic contamination of food, especially fresh vegetables, is not limited to personal hygiene during food preparation but is also widely dependent on the source of the food and the handling it undergoes before it gets to the consumer. The objective of the present study was to evaluate parasitic contamination in eight common raw vegetables in Tabuk, Kingdom of Saudi Arabia. A total of 400 samples of raw vegetables obtained from wholesale and retail markets were examined for helminth eggs and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 15 publications
9
23
1
2
Order By: Relevance
“…A portion (usually 50-250 g) of each vegetable or fruit sample is washed separately in a container containing some chemical solutions. The most widely used solutions are normal saline [14,[17][18][19][20] and phosphate-buffered saline [12,[21][22][23][24]. The commonly used solutions are glycine [11,25], sodium dodecyl sulfate [26], Alconox ® [27], and Tween 80 [28].…”
Section: Detection Methods Of Intestinal Protozoan Parasites Contaminmentioning
confidence: 99%
See 3 more Smart Citations
“…A portion (usually 50-250 g) of each vegetable or fruit sample is washed separately in a container containing some chemical solutions. The most widely used solutions are normal saline [14,[17][18][19][20] and phosphate-buffered saline [12,[21][22][23][24]. The commonly used solutions are glycine [11,25], sodium dodecyl sulfate [26], Alconox ® [27], and Tween 80 [28].…”
Section: Detection Methods Of Intestinal Protozoan Parasites Contaminmentioning
confidence: 99%
“…More than one smear slide is usually prepared for each specimen to allow its precise detection [12,26]. Oocysts or cysts can be detected microscopically based on their morphological features [14,17,20,29], using Lugol's iodine [12,14,29] or modified Ziehl-Neelsen staining (or any other staining technique) [14,19,26]. The extraction of the parasitic DNA from the sediment, followed by the PCR amplification of specific genes, is also efficiently used for the protozoan detection in vegetable and fruit samples [22,24].…”
Section: Detection Methods Of Intestinal Protozoan Parasites Contaminmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies over the world have shown that many species of enteric helminthes and protozoa can infect humans who consume contaminated, improperly washed fruits and vegetables ( Al-Shawa and Mwafy, 2007 ; Adanir and Tasci, 2013 ; Ismail, 2016 ). Vegetables become contaminated with different parasitic phases (cyst, oocyst, ova, larvae) during irrigation by waste water or by direct contamination from animals and humans during harvesting, packing, transport processing, distribution, and marketing ( Amoah et al, 2007 ; Gabre and Shakir, 2016 ). Many countries around the world have realized the importance of evaluating the role of raw vegetables in the transmission of intestinal parasites ( Abougrain et al, 2010 ; Omowaye and Audu, 2012 ; Chau et al, 2014 ; Khan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%